The quality of the sinthome - Gaetano, Guillermo (Facultad de Psicología (Universidad Nacional de La Plata, Argentina), 2021)
This article seeks to recover the qualitative characteristics of the sinthome outlined by Lacan. In this tour we intend to describe it, both by its uniqueness and in the context of the other elements of its kind: the fourth strings to the RSI knot. Whithin this category, the nominations -inhibition, symptom and anguish- will have a preponderant place of reference since they undergone an important conceptual revision by Lacan during the period of the emergence of the sinthome.